Participation in communication and decisions with regards to nursing care: the role of children - Lee, Siew Pien (2018)
Background: There is growing body of literature that emphases the child’s right to information and participation in decision related to health care. There is the need for research centred on understanding children’s experiences of participation in decisions regarding their nursing care and within the Malaysian health care setting.